A View of Time in Open and Distance Learning - Hoo Fang Jing; Mohd Amin Mohd Noh; Raihan Ibrahim (EDUTECH, 2022)
When sudden shifts from purely campus-centred of higher education to Open and Distance Learning (ODL) using information and communication technologies were done drastically in early 2020, there were many issues highlighted pertaining to ODL and one of it is time. And for almost a year now, presuming ODL has been done over some time, both instructors and learners should be able to adapt and adopt to the new education system. The purpose of this study was to identify instructors’ and learners’ ability to allocate time in open and distance learning (ODL). The study was conducted with 320 respondents and the instrument used was questionnaires. The results showed that ODL instructors and learners were challenged with a range of obstacles to prioritise tasks and allocate time accordingly in their course of teaching and learning. The most reported challenges were first, least time spent to interact with students or teachers while teaching and learning on ODL, and secondly, least time spent with family members while teaching and learning on ODL. It was found that both instructors and learners from public and private higher learning institution were still facing problems in allocating time when adopting the practice of ODL. In short, time allocation in prioritising tasks is still an obstruction to achieve effective and balanced teaching and learning system with ODL that satisfies the desire of the instructors and learners.